2016
DOI: 10.1038/aps.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin suppresses TGF-β mediated epithelial-mesenchymal transition in pulmonary fibrosis through a Smad-dependent pathway

Abstract: Aim: Paeoniflorin has shown to attenuate bleomycin-induced pulmonary fibrosis (PF) in mice. Because the epithelial-mesenchymal transition (EMT) in type 2 lung endothelial cells contributes to excessive fibroblasts and myofibroblasts during multiple fibrosis of tissues, we investigated the effects of paeoniflorin on TGF-β mediated pulmonary EMT in bleomycin-induced PF mice. Methods: PF was induced in mice by intratracheal instillation of bleomycin (5 mg/kg). The mice were orally treated with paeoniflorin or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 49 publications
4
83
0
Order By: Relevance
“…TGF‐β is regarded as the causative cytokine for induction of both in vitro and in vivo EMT, and TGF‐β can be secreted by macrophages, lung epithelial cells, and fibroblasts during the development of pulmonary fibrosis (Halwani et al, ). The TGF‐β/Smad2 signaling pathway has been reported to induce EMT and fibrosis through Smad‐ or non‐Smad signaling pathways (Ji et al, ; Zhang et al, ). It has been demonstrated that TGF‐β induces EMT in alveolar epithelial cells both in vivo and in vitro via Smad2 activation (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β is regarded as the causative cytokine for induction of both in vitro and in vivo EMT, and TGF‐β can be secreted by macrophages, lung epithelial cells, and fibroblasts during the development of pulmonary fibrosis (Halwani et al, ). The TGF‐β/Smad2 signaling pathway has been reported to induce EMT and fibrosis through Smad‐ or non‐Smad signaling pathways (Ji et al, ; Zhang et al, ). It has been demonstrated that TGF‐β induces EMT in alveolar epithelial cells both in vivo and in vitro via Smad2 activation (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It does appear, based on the findings in this study that PF might be the major phytochemical entity in Paeonia lactiflora and Astragalus membranaceus extracts responsible for the anti-fibrotic bioactivity. This views is supported by the fact that it had similar effects on both pulmonary [5,6] and renal interstitial fibrosis [7].…”
Section: Discussionmentioning
confidence: 81%
“…Paeoniflorin (PF), isolated from Corte moutan, is a major bioactive compound with antiinflammatory and immune-regulatory effects [3,4]. The anti-fibrotic effect of PF has been studied on both pulmonary [5,6] and renal interstitial fibrosis [7]. Studies of the effect of PF'on Schistosomiasis japonica-induced liver fibrosis have also been carried out [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may be effective in preventing adhesion by inhibiting the inflammatory reaction and cytokines induction caused by injury. In the IFRD, some constituents including Codonopsis Radix (Dangshen) [28], Atractylodes Rhizoma (Baizhu) [29], and Paeoniae Rubra Radix (Chishao) [30] were reported to have anti-inflammatory and antioxidative effects. Jia and He [31] indicated that paeoniflorin, a chemical constituent of Paeoniae Rubra Radix, ameliorated disease in rat models of rheumatoid arthritis by suppressing oxidative stress and inflammation and reducing COX-2 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast cells are crucial for ECM deposition; once activated, they differentiate into myofibroblasts that express α -SMA [30]. A hallmark of myofibroblast activation, α -SMA, is typically used to assess the level of fibrosis [36], and positive staining of α -SMA reveals the development of fibrosis.…”
Section: Discussionmentioning
confidence: 99%